Technical Experiences on a Microservices-oriented Transformation using Open Source Software - Benitez-Davalos, Walter; López-Pires, Fabio; Cabañas, David; Bogado-Sarubbi, Yessica (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware), 2019)
Adopting emerging computing paradigms such as cloud applications include challenges associated to transform legacy software to essential characteristics of the mentioned computing model, e.g. on-demand self-service, broad network access, resource pooling, rapid elasticity and measured services. This paper presents a summary of technical experiences on applying one of the most popular approaches to address transformation of legacy software to cloud-native applications: a microservice-oriented architecture with connections to legacy systems through anti-corruption layers. Several technical considerations are presented, focusing on Open Source Software to include particular features on modern development practices as well as solving issues related to the cloud-native transformation.